(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2021)
Productivity is a ratio of monetary value of output to the monetary value of input. Higher the productivity ratio of a company denotes more efficiently the company has used its resources. In the present research, an attempt has been made to measure, analyse and compare productivity of four companies of IT sector during the period from 2010-11 to 2017-18 i.e. for eight years. Intra-company comparison has been drawn with the help of chi-square test and results indicate that null hypothesis is accepted in all the cases of IT companies. Inter-company comparison has been drawn with the help of Kruskal Wallis One Way ANOVA Test and results indicate that null hypothesis is rejected. After analysing the average overall productivity it is observed that overall productivity is almost one that means IT sector companies are not optimally utilizing its resources, it is just meeting its cost. It is recommended that the companies should take steps to maintain the productivity ratio high in future by optimally utilizing the resources.